If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7(9x + 43) = 0 Reorder the terms: -7(43 + 9x) = 0 (43 * -7 + 9x * -7) = 0 (-301 + -63x) = 0 Solving -301 + -63x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '301' to each side of the equation. -301 + 301 + -63x = 0 + 301 Combine like terms: -301 + 301 = 0 0 + -63x = 0 + 301 -63x = 0 + 301 Combine like terms: 0 + 301 = 301 -63x = 301 Divide each side by '-63'. x = -4.777777778 Simplifying x = -4.777777778
| v^2-7v=0 | | -6x+12+20=-2 | | 4x-1+2x-1=5x | | 5=85+(15+8) | | 4=85+(15+8) | | 2(2x-1)-6=-x+2 | | 6a+2+2a=18 | | b=85+(15+8) | | 12x-2(4x-6)=24 | | 12-4n=-15-n | | m+0.5=3m+0.9 | | 4y-6=-13-3y | | 2x=(5x+5) | | -9x^2+30x-25=0 | | (3x+2)=(4x-4) | | 8x+7=4x+11 | | -0.2x=4.875 | | 4(5+3n)-4=-72 | | -0.2x-4=.875 | | 5.30p+2.50=55.20 | | (3y-8)(y+3)= | | 9x+45-5x=46+3x | | 7+20s=115 | | -4m+5+6m=-3 | | 0.5x=-4.71 | | 0.5=-4.71 | | 9[(3+3)*5]=270 | | 3x+4+8x= | | 40-2x=7x+18 | | -1.2=-0.6x | | 9-8x=39-15x | | -3xy+12+(5xy+4)= |